Nanodelivery Systems Delivering Hypoxia-Inducible Factor-1 Alpha Short Interfering RNA and Antisense Oligonucleotide for Cancer Treatment - Yan, Yan; Li, Houli; Yao, Hongping; Cheng, Xiaoliang (Frontiers in Nanotechnology, 2022)
Hypoxia inducible factor (HIF) which plays crucial roles in oxygen homeostasis contributes to immunosuppression, tumor angiogenesis, multidrug resistance, photodynamic therapy resistance, metastasis. HIF as a therapeutic target has attracted scientists’ strong academic research interests. Short interfering RNA (siRNA) and antisense oligonucleotide (ASO) are the more promising and broadly utilized methods for oligonucleotide based therapy. Their physiochemical characters of hydrophilic, negative charged and high molecular weight make them impossible to cross the cell membrane. Moreover, siRNA and ASO are subjected to a rapid deterioration in circulation and couldn’t translocate into nuclear. Delivery of siRNA and ASO to specific gene target should be realized without off-target gene silencing and affecting the healthy cells. Nanoparticles as vectors for delivery of siRNA and ASO possess great advantages and flourish in academic research. In this review, we summarized and analyzed regulation mechanisms of HIF under hypoxia, significant role of HIF on promoting tumor progress, and recent academic research on nanoparticle based delivery of HIF siRNA and ASO for cancer immunotherapy, anti-angiogenesis, reversal of multi-drug resistance and radioresistance, potentiating photodynamic therapy, inhibiting tumor metastasis and proliferation, and enhancing apoptosis are reviewed in this thesis. Furthermore, we hope to provide some rewarding suggestions and enlightenments for targeting HIF gene therapy.